ИНФОРМАЦИОННО-АНАЛИТИЧЕСКОЕ ОБЕСПЕЧЕНИЕ МОНИТОРИНГА СОСТОЯНИЯ И ИСПОЛЬЗОВАНИЯ ПРИРОДНЫХ РЕСУРСОВ - Митракова О.В.; Аракчеев Д.Б. (My University, 2006)
Paper is devoted to main aspects of development and application of information and analytical systems in the monitoring of natural resources. Considered are results of theoretical and technological research in the development of a new powerful platform for construction of multi-tie computer systems. Presented are of its application.
Keywords: 330.15:025.4.03